The Effect of Transformational Leadership Style and Job Satisfaction on Work Engagement, Mediated by Perceived Organizational Support at PT. Viva Vegas Ventury Denpasar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee work engagement is the extent to which employees are able and willing to commit to an organization, and the results of such commitment can be observed in their performance and tenure. This study aims to examine the effect of transformational leadership style and job satisfaction on work engagement through perceived organizational support at PT. Viva Vegas Ventury Denpasar. The study was conducted at PT. Viva Vegas Ventury Denpasar with a total sample of 45 employees. The sampling technique used was saturated sampling. Data were collected through observation, interviews, questionnaires, and documentation. The analytical method employed was a variance-based structural equation modeling, commonly known as Partial Least Squares (PLS). The results of the analysis show that transformational leadership style, job satisfaction, and perceived organizational support have a positive and significant effect on work engagement. Transformational leadership style and job satisfaction also have a positive and significant effect on perceived organizational support. Moreover, perceived organizational support mediates the influence of transformational leadership style and job satisfaction on work engagement.